Decadal changes in dissolved inorganic carbon in the Pacific Ocean. Issue 1 (29th January 2013) - Kouketsu, Shinya; Murata, Akihiko; Doi, Toshimasa
<x xml:space="preserve">Abstract</x> [1] Using high‐quality data sets obtained about a decade apart, we examined the changes of dissolved inorganic carbon in the Pacific Ocean, separating anthropogenic and natural CO2. Observations along three transoceanic sections along 47°N, 179°E, and 17°S showed both decadal increases (>20 µmol kg–1) and decreases (<−20 µmol kg–1) of anthropogenic CO2 in thermocline waters. As a result, the decadal‐scale storage of anthropogenic CO2 north of 40°N in the North Pacific was close to ±0 mol m–2 a–1, except in the western subarctic Pacific. In contrast, in subtropical regions of both hemispheres, we found an increasing trend of >10 µmol kg–1 in oceanic uptake of anthropogenic CO2, reflecting accumulation in mode waters. Along 17°S, increases of anthropogenic CO2 were >20 µmol kg–1, larger than expected from increases of anthropogenic CO2 in the atmosphere. The annual water‐column inventories of anthropogenic CO2 changes calculated in 20° longitudinal or 10° latitudinal bands throughout the Pacific Ocean revealed relatively high values (>0.7 mol m–2 a–1) in the subtropical regions of both hemispheres and low values in the tropical Pacific. This distribution pattern is similar to previous estimates for the Anthropocene, implying that the redistribution processes of anthropogenic CO2 have not changed on a basin scale over the last decade. We estimated the total anthropogenic and natural CO2 storage in the Pacific Ocean to be 8.4 ± 0.5 and 0.6 ± 0.4 Pg carbon decade–1, respectively.